Police Legitimacy and Citizen Cooperation in China: testing an Alternative Model - Sun, Ivan Y. (Asian journal of criminology, 2018)
Past research has identified several mechanisms of promoting citizen cooperation with the police, with Tyler’s process-based policing model being one of the most frequently tested frameworks in this line of inquiry. Using data collected from a large sample of residents in a large Chinese city, this study assesses an alternative model of Tyler’s work proposed by Tankebe (2013), positing that police legitimacy, embodied in four aspects of procedural justice, distributive justice, effectiveness, and lawfulness, affects people’s obligation to obey the police, which further influences their cooperation with the police. Results from second-order confirmatory factor analysis and structural equation modeling analysis suggested that Tankebe’s work is supported by the Chinese data. Implications for future research and policy are discussed.